The effectiveness of blog informatic zone to the information management students in UiTM, Sarawak / Mohd Rafiz Salji … [et.al.]. - Salji, Mohd Rafiz; Sulaiman, Sharin; Mohd Jawi, Abdul Ismail (2010)
Information is very important nowadays by delivering message from sender to recipient through variety of mediums. By using information, everybody can be able to interact between each other and it will create network sharing. However, there are difficult to share information using printed form and when the records keep in manual format, the ICO information was not distribute in rapid, effective and efficient way. Objective of this research was to study the students' opinion on the blog Informatic Zone. Students in UiTM, Kota Samarahan campus have answered a questionnaire regarding usage and effect of the blog Informatic Zone. Towards identifying students usage, it focused on how many respondents have their own blog, identifying respondents awareness on objectives, where they know the existence, how many times they serve in a week, how long they surf, did respondents give any comment and do they satisfied with the information posted in the blog Informatic Zone. On effect to the students, it would discussed on if the blog Informatic Zone can improve social networking, obtain friends, opinion on effectiveness of blog, improve sense of awareness, improve writing skill and opportunity to share knowledge. In conclusion, respondents understood the purpose of usage and can identified the effect of the blog Informatic Zone.